2015
DOI: 10.1136/bmjopen-2015-008194
|View full text |Cite
|
Sign up to set email alerts
|

Use and safety of azithromycin in neonates: a systematic review

Abstract: ObjectivesTo identify the use and adverse drug reactions associated with azithromycin in neonates.SettingDatabases MEDLINE (1948–August 2015), EMBASE (1980–August 2015) and Pubmed (August 2015) were searched for studies on azithromycin in neonates.ParticipantsAll studies involving neonates (<28 days old) who have received at least a single dose of azithromycin for which safety was evaluated.Primary and secondary outcome measuresThe primary outcome was adverse event (AE) associated with use of azithromycin. Use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 33 publications
(33 reference statements)
0
52
0
4
Order By: Relevance
“…The association was strongest if the exposure occurred in the first two weeks after birth [57]. There are no reported cases of cardiac side effects as seen in adults, in infants treated with azithromycin [56].…”
Section: Macrolidesmentioning
confidence: 90%
See 2 more Smart Citations
“…The association was strongest if the exposure occurred in the first two weeks after birth [57]. There are no reported cases of cardiac side effects as seen in adults, in infants treated with azithromycin [56].…”
Section: Macrolidesmentioning
confidence: 90%
“…In a subsequent systematic review of 11 trials which included 473 infants azithromycin was demonstrated to reduce BPD in extremely low birth weight (ELBW) infants (RR 0.83, 95% CI 0.72 -0.98, p=0.02) [56]. There was no significant difference in the incidence of elevated liver enzymes, but there were four cases of hypertrophic pyloric stenosis [56].…”
Section: Macrolidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods of pharmacological treatment. In prophylactic procedure, attempts are being made to use retinol, caffeine citrate, inhaled nitric oxide, beta-adrenomimetics, ipratropium bromide, diuretics and in newborns with confirmed colonization or infected with Ureaplasma urealyticum, also macrolide antibiotics, mainly azithromycin [50,51]. According to evidence-based data, GCSs are the unique recommended method of prevention of BPD in children and can significantly improve the short-term prognosis of patients [52][53][54][55][56].…”
Section: Current and Future Pharmacological Methods Of Prevention Andmentioning
confidence: 99%
“…Azithromycin exerts a bacteriostatic effect against many Gram-positive and Gram-negative bacte-ria (Mcmullan and Mostaghim, 2015). However, oral and intravenous formulations of azithromycin are not recommended for children less than 6 months and 16 years, respectively, due to the lack of adequate clinical studies in this population (Smith et al, 2015).…”
Section: Pharmacokinetics Of Azithromycinmentioning
confidence: 99%